Intra-union conflict and the 1970 dock strike in Britain. (3rd March 2020) - Taylor, Greig
ABSTRACT: The docks are one of the most academically scrutinised sectors of the British economy and, due to the industry's historical reputation for strike-proneness, episodes of workplace conflict are generally popular sources for research. Nevertheless, one dispute remains curiously under-examined – the 1970 national dock strike. This is particularly remarkable since it constituted the first national strike in the industry for nearly half a century, lasted almost three weeks, led to the declaration of a State of Emergency and required a government-sponsored inquiry to reach a resolution. On the surface, it was provoked by disagreement between the national employers' association and the union over basic weekly wage bargaining. Behind the scenes, however, the course, nature and outcome of the dispute is best understood in the context of the relationship between the membership and officialdom of the union, which was rooted in a history of antagonism, and the revolutionary technological changes taking place in cargo handling at this time. What follows is a detailed account of the 1970 national dock strike and the events surrounding it, considered in the context of the literature relating to hierarchical divisions in trade union organisations. Abbreviations: LMC: Local Modernisation Committee NAPE: National Association of Port Employers NASDU: National Amalgamated Stevedores and Dockers Union NDLB: National Dock Labour Board NDLS: National Dock Labour Scheme NJC: National Joint Council for the Port Transport Industry NPSSC: National Ports Shop Steward Committee TGWU: Transport and General Workers' Union TUC: Trades Union Congress TUR: Temporary Unattached Register